Atlas of robotic urologic surgery - Su, Li-Ming (Springer, 2011)
The Atlas of Robotic Urologic Surgery provides a detailed, step-by-step guide to common robotic urologic procedures for the purpose of helping novice surgeons in their transition to robotic surgery and seasoned robotic surgeons to refine their surgical technique and expand their repertoire of robotic procedures. In addition, less commonly performed robotic procedures such as those for male infertility, pelvic organ prolapse, urinary tract reconstruction and pediatrics are included. Each chapter is written by the thought leaders in robotic urologic surgery with descriptive step-by-step text, complimented by figures and intraoperative photographs detailing the nuances of each procedure. Emphasis is placed on operative setup, instrument and equipment needs and surgical techniques for both the primary surgeon as well as the operative assistant. The use of ancillary equipment and robotic instrument and endoscope exchanges are highlighted throughout the procedural text by tables designed to aid surgeons and their teams in improving efficiency. This volume will provide unique insights into robotic urologic surgery and reduce the learning curve of accomplishing these increasingly popular procedures.